PERILAKU HIDUP BERSIH DAN SEHAT PADA RUMAH SAKIT DAN MASYARAKAT DI SMA NEGERI 2 BANGKINANG - Wiwik Suryandartiwi; Agus Salim (LPPM Universitas Awal Bros, 2021)
The PHBS arrangement in the household is the most important point in the movement. With the achievement of healthy household conditions through the PHBS arrangement, each family member is expected to be willing and able to have an active role in practicing clean and healthy living behavior at the community level. This paper aims to increase understanding of knowledge about patterns of clean and healthy living behavior for many people both in daily life. In addition, it is also expected to be able to help in applying it in everyday life. The target in this service is the students of SMA Negeri 2 Bangkinang. However, few students attended and the event was not on schedule because students did not arrive on time. This community service provides experience to students in carrying out activities such as guiding activities, giving remarks from the committee, the committee providing direction to activities and also providing experience to students in making activity reports.